Development of bioartificial myocardium by electrostimulation of 3D collagen scaffolds seeded with stem cells - Alain Carpentier; Juan C. Chachques; Fabien Legrand; Samira Benadda; Nermine Lila; Kanwal Haneef (Heart International, 2012)
Electrostimulation (ES) can be defined as a safe physical method to induce stem cell differentiation. The aim of this study is to evaluate the effectiveness of ES on bone marrow mesenchymal stem cells (BMSCs) seeded in collagen scaffolds in terms of proliferation and differentiation into cardiomyocytes. BMSCs were isolated from Wistar rats and seeded into 3D collagen type 1 templates measuring 25 x 25 x 6 mm. Bipolar in vitro ES was performed during 21 days. Electrical impedance and cell proliferation were measured. Expression of cardiac markers was assessed by immunocytochemistry. Viscoelasticity of collagen matrix was evaluated. Electrical impedance assessments showed a low resistance of 234±41 Ohms which indicates good electrical conductivity of collagen matrix. Cell proliferation at 570 nm as significantly increased in ES groups after seven day (ES 0.129±0.03 vs non-stimulated control matrix 0.06±0.01, P=0.002) and after 21 days, (ES 0.22±0.04 vs control 0.13±0.01, P=0.01). Immunocytochemistry of BMSCs after 21 days ES showed positive staining of cardiac markers, troponin I, connexin 43, sarcomeric alpha-actinin, slow myosin, fast myosin and desmin. Staining for BMSCs marker CD29 after 21 days was negative. Electrostimulation of cell-seeded collagen matrix changed stem cell morphology and bio- chemical characteristics, increasing the expression of cardiac markers. Thus, MSC-derived differentiated cells by electrostimulation grafted in biological scaffolds might result in a convenient tissue engineering source for myocardial diseases.